Integral Emotions and Incidental Emotions of Consumers in Impulse Buying Behavior Online - Erna Ferrinadewi (Publikasi Indonesia, 2024)
Impulsive buying has been vigorously studied from different perspectives. In the science of Consumer Behavior, impulsive buying depicts a consumer’s buying decision which is spontaneous and quick, quite often without the presence of any cognitive activity. Prior studies often observed how this impulsive buying is being influenced by consumer’s emotions, but only a few studies observe how Integral Emotions and Incidental Emotions influence the collective decision of impulsive buying and its emotional impact. Involving 100 respondents with prior experiences of impulsive buying, the data would then be analyzed using the Partial Leas Square-SEM after considering the ability of this statistical model to analyze data below 500 respondents. Results showed that there is a significant negative relationship between Incidental Emotion the impulsive buying, but a negative influence towards Integral Emotion on the impulsive buying decision. Besides that, there is a significant positive influence of impulsive buying towards the emotion afterwards.